Dielectric surface loss in superconducting resonators with flux-trapping holes. (19th August 2016) - Chiaro, B; Megrant, A; Dunsworth, A; Chen, Z; Barends, R; Campbell, B; Chen, Y; Fowler, A; Hoi, I C; Jeffrey, E; Kelly, J; Mutus, J; et al.
Abstract: Surface distributions of two level system (TLS) defects and magnetic vortices are limiting dissipation sources in superconducting quantum circuits. Arrays of flux-trapping holes are commonly used to eliminate loss due to magnetic vortices, but may increase dielectric TLS loss. We find that dielectric TLS loss increases by approximately 25% for resonators with a hole array beginning 2 μ m from the resonator edge, while the dielectric loss added by holes further away was below measurement sensitivity. Other forms of loss were not affected by the holes. Additionally, we estimate the loss due to residual magnetic effects to be 9 × 10 − 10 μ T − 1 for resonators patterned with flux-traps and operated in magnetic fields up to 5 μ T . This is orders of magnitude below the total loss of the best superconducting coplanar waveguide resonators.